First Principles Study of the Stability and Diffusion Mechanism of a Carbon Vacancy in the Vicinity of a SiO2/4H–SiC Interface. Issue 17 (12th August 2019) - Alsnani, Hind; Goss, Jonathan P.; Briddon, Patrick; Rayson, Mark; Horsfall, Alton B.
Abstract : The carbon vacancy in bulk 4H‐SiC and in the vicinity of an SiO2 /(0001)‐4H‐SiC interface using density‐functional theory is studied. It is found that the migration is hindered in the immediate vicinity of the interface, with the energy barrier for diffusion being ≈15% greater than the same defect in bulk 4H‐SiC. Herein, it is shown that the increased barrier is a consequence of the stabilization of the vacancy in the immediate interface due to a combination of strengthened reconstructions and interfacial relaxation, coupled with the destabilization of the transition‐state structure. Abstract : The majority of electronically active defects in SiC are located deep within the bandgap, thereby degrading the carrier transport properties of SiC. This study compares the diffusion of a carbon vacancy in different (0001)‐layers relative to a SiO2 /SiC interface using the density‐functional theory simulations. The results show that vacancies in the upper layers are stabilized due to stronger bonding and interfacial relaxation.